Experimental study of the thermal performance of a novel plate type heat exchanger with phase change material. (September 2020) - Lin, Wenzhu; Zhang, Wenbo; Ling, Ziye; Fang, Xiaoming; Zhang, Zhengguo
Highlights: The pillow plate heat exchanger with phase change material was investigated. A novel pillow plate heat exchanger with two flowing channels distributed in the plate was designed. The thermal performance of the novel latent heat thermal energy storage heat exchanger was studied. Abstract: The paper presents an experimental investigation of a novel latent heat thermal energy storage system. The new energy storage unit is a pillow plate type heat exchanger with multi flowing channels, while the phase change material (PCM) - sodium acetate trihydrate (SAT) works as the energy storage medium. Water as the working fluid, flows in the distributed channels inside the plates to charge or discharge the system. The thermal performance of the latent heat thermal energy storage system was evaluated, including the outlet temperature of water, thermal power and energy, effectiveness and heat transfer coefficient. Results from the experimental analysis showed that the released energy of system can reach up to 6.3 MJ with the average power 4 kW. The overall heat transfer coefficient and heat transfer area ranges from about 25 to 70 W/k from 100 to 500 L/h flow rate. The pillow plate type heat exchanger showed good thermal performance, offering high heat transfer rate under the compact structure. Also, the novel multi flowing channels designed heat exchanger provides more flexibility and adaptability for real application, it has a wide application prospect in the fields of solar water energy storage, heat pump water heater system and waste heat recovery system.